Procedura wymiaru i wykonania kar dyscyplinarnych wobec skazanych na karę pozbawienia wolności. Część I art. 144 k.k.w.–art. 145 k.k.w. - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article examines issues related to the procedure for the levels and enforcement of disciplinary penalties against convicts serving prison sentences. A particular emphasis is put on the collection of appropriate evidence, conduct of investigations, ensuring the right to defence, and criminal penalty directives. The author also gives alot of attention to persons authorised to establish the level of penalty and the scope of their competence as well as the procedure for appeal from and control of decisions taken as part of disciplinary actions.
Keywords: naruszenie; kara dyscyplinarna; skazany; dochodzenie; organ karzący; postępowanie karne